2017
DOI: 10.1080/15548627.2017.1297907
|View full text |Cite
|
Sign up to set email alerts
|

The autophagy machinery restrains iNKT cell activation through CD1D1 internalization

Abstract: Invariant natural killer T (iNKT) cells are innate T cells with powerful immune regulatory functions that recognize glycolipid antigens presented by the CD1D protein. While iNKT cell-activating glycolipids are currently being explored for their efficacy to improve immunotherapy against infectious diseases and cancer, little is known about the mechanisms that control CD1D antigen presentation and iNKT cell activation in vivo. CD1D molecules survey endocytic pathways to bind lipid antigens in MHC class II-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…Although ESCRT, HOPS, and SNARE complex proteins all have been reported to regulate autophagy 50 , knockdown of macroautophagy genes, such as Atg7 , did not have a strong effect on iNKT cell responses, consistent with a recent report 51 . A more recent study, however, indicated a role for Atg5 in inhibiting CD1d antigen presentation 52 . Similar to Vps11 and Snap29 , Dock2 gene knockdown also reduced CD1d accumulation in lysosomes.…”
Section: Discussionmentioning
confidence: 98%
“…Although ESCRT, HOPS, and SNARE complex proteins all have been reported to regulate autophagy 50 , knockdown of macroautophagy genes, such as Atg7 , did not have a strong effect on iNKT cell responses, consistent with a recent report 51 . A more recent study, however, indicated a role for Atg5 in inhibiting CD1d antigen presentation 52 . Similar to Vps11 and Snap29 , Dock2 gene knockdown also reduced CD1d accumulation in lysosomes.…”
Section: Discussionmentioning
confidence: 98%
“…This beneficial role of the macroautophagy machinery for cross-presentation is counterbalanced by its role in restricting MHC class I and MHC class I-like antigen presentation on the cell surface of antigen-presenting cells (APCs) by endocytosis [ 50 , 51 ]. Indeed, the net outcome of deficiency in Atg components of the LC3 lipidation complex in myeloid or dendritic cells is an elevated, often CD8 + T cell-mediated adaptive immune control or immunopathology [ 52 , 53 ].…”
Section: Exo- and Endocytosis With Atg Modules For Mhc Class I Antmentioning
confidence: 99%
“…This results in increased priming of influenza A virus-specific CD8 + T cells and decreased infection associated viral titers and pathology in the absence of LC3 lipidation in dendritic cells. Similar to this regulation of classical MHC class I molecule endocytosis, the LC3 lipidation machinery also supports internalization of the non-classical MHC class I-like molecule, CD1d [ 51 ]. This leads to enhanced glycolipid presentation on CD1d to NKT cells and improved NKT cell-mediated immune control of the Sphingomonas paucimobilis infection.…”
Section: Exo- and Endocytosis With Atg Modules For Mhc Class I Antmentioning
confidence: 99%
“…This resulted in increased CD8 + T cell stimulation in vitro and elevated CD8 + T cell responses to influenza A virus (IAV) and lymphocytic choriomeningitis virus infection in vivo , as well as improved immune control of IAV. However, not only classical MHC class I molecules are affected by diminished clathrin-dependent receptor internalization in the absence of Atg8/LC3 lipidation but also the non-classical MHC class I molecule CD1d gets stabilized on the cell surface of Atg5-deficient DCs ( 49 ). These non-classical MHC class I molecules present glycolipids to NKT cells ( 50 ).…”
Section: Atg Proteins In Receptor Internalization and Mhc Class I Antmentioning
confidence: 99%
“…These non-classical MHC class I molecules present glycolipids to NKT cells ( 50 ). The increased CD1d surface stabilization in the absence of Atg-dependent internalization led to increased NKT cell stimulation in vitro and in vivo ( 49 ). Furthermore, the NKT cell-dependent pathogen Sphingomonas paucimobilis was more efficiently restricted in mice with Atg5 deficiency in their DCs.…”
Section: Atg Proteins In Receptor Internalization and Mhc Class I Antmentioning
confidence: 99%